STUDY OF PRESCRIPTION PATTERNS OF ANTIHYPERTENSIVE AGENTS IN TERTIARY CARE TEACHING HOSPITAL - Fadil Salmani; Shaktibala Dutta; Dr. Jyotsna Sharma; Dr. Srihari Dutta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Hypertension is a major public health concern requiring effective pharmacological management. This study aimed to evaluate the prescribing patterns of antihypertensive drugs and adherence to treatment guidelines in a tertiary care hospital. Methods: A cross-sectional observational study was conducted from June 2023 to June 2024 in the outpatient department of medicine at Santosh Medical College and Hospital, Ghaziabad. Ethical approval was obtained, and 1027 hypertensive patient prescriptions were analyzed based on predefined inclusion and exclusion criteria. Prescription data were assessed using WHO drug use indicators, and statistical analysis was performed using SPSS, with categorical variables analyzed via the chi-square test. Results: A total of 2978 drugs were prescribed, of which 1086 (36.5%) were antihypertensive agents, with an average of 1.67 antihypertensive drugs per prescription. Only 24.40% were prescribed by their generic name, and fixed-dose combinations (FDCs) were included in 41.70% of prescriptions. Injectable antihypertensive use was minimal (2.11%), while 68.82% of antihypertensive drugs were from the National List of Essential Medicines (NLEM 2020). Polypharmacy was observed in 91.70% of cases. The most commonly prescribed antihypertensive drug classes were Angiotensin Receptor Blockers (40.15%) and Calcium Channel Blockers (38.21%), with Telmisartan (37.48%) and Amlodipine (31.31%) being the most frequently prescribed individual drugs. Dual therapy was the most common treatment approach (45.28%), followed by monotherapy (39.73%). The chi-square test revealed no significant association between therapy type and drug class distribution (p = 0.648). Conclusion: The study highlights prescribing trends in hypertension management, emphasizing a preference for brand-name medications, a high prevalence of polypharmacy, and frequent use of combination therapy. Addressing gaps in generic prescribing and ensuring rational drug use can optimize hypertension treatment outcomes and reduce healthcare costs.